Dental pulp stem cells and Bonelike® for bone regeneration in ovine model. Issue 1 (22nd December 2018) - Campos, J M; Sousa, A C; Caseiro, A R; Pedrosa, S S; Pinto, P O; Branquinho, M V; Amorim, I; Santos, J D; Pereira, T; Mendonça, C M; Afonso, A; Atayde, L M; et al.
Abstract: Development of synthetic bone substitutes has arisen as a major research interest in the need to find an alternative to autologous bone grafts. Using an ovine model, the present pre-clinical study presents a synthetic bone graft (Bonelike ® ) in combination with a cellular system as an alternative for the regeneration of non-critical defects. The association of biomaterials and cell-based therapies is a promising strategy for bone tissue engineering. Mesenchymal stem cells (MSCs) from human dental pulp have demonstrated both in vitro and in vivo to interact with diverse biomaterial systems and promote mineral deposition, aiming at the reconstruction of osseous defects. Moreover, these cells can be found and isolated from many species. Non-critical bone defects were treated with Bonelike ® with or without MSCs obtained from the human dental pulp. Results showed that Bonelike ® and MSCs treated defects showed improved bone regeneration compared with the defects treated with Bonelike ® alone. Also, it was observed that the biomaterial matrix was reabsorbed and gradually replaced by new bone during the healing process. We therefore propose this combination as an efficient binomial strategy that promotes bone growth and vascularization in non-critical bone defects.